Petrological, mineralogical, and geochemical compositions of coal in the Ombilin Basin, West Sumatra, Indonesia - Patria, Aulia Agus (Elsevier, 2022)
Coal deposits have received considerable attention in recent years owing to their by-product waste being a promising alternative source of critical elements. The Ombilin Basin is well known as one of the largest coal-producing basins in Indonesia. This study investigated the petrological, mineralogical, and geochemical compositions of four Eocene coal seams in Ombilin Basin basement rock, and their relevance regarding critical element enrichment. Samples of coal and basement rock from the Ombilin Basin were analyzed using thin- and polished-section scanning electron microscope energy-dispersive X-ray spectroscopy, inductively coupled plasma atomic emission spectroscopy, and inductively coupled plasma mass spectrometry. Coals from the Ombilin Basin are high-volatile bituminous C coals with mean random vitrinite reflectance values of 0.58–0.66. Vitrinite content is the most dominant maceral (61.06 vol mmf), followed by liptinite (24.95 vol mmf), and inertinite (13.75 vol mmf). Minerals observed in the coal samples comprised pyrite, quartz, and clay. Pyrite was present as discrete crystals, massive crystals, framboidal pyrite, and cell-filling on other macerals. Both syngenetic and epigenetic pyrite was found in the Ombilin coal. Based on the petrological and mineralogical analyses, basement rock in the Ombilin Basin can be divided into four groups: granodiorite, andesite-basaltic, marble, and meta-sediment. In comparison with World Hard Coal and common Chinese coals, some layers/partings in the coal seams in the Ombilin Basin are enriched in U (37.6 ppm), V (175 ppm), and total rare earth elements and yttrium (REY; 126.15 ppm). REY-bearing minerals in the Ombilin coal samples were attributed to clay and sulfide minerals, while others were found as dispersed and scattered, indicating that REY are organically bound. Inorganic materials in Ombilin coal deposits have mainly intermediate-felsic provenance, are derived from Cretaceous granitoid rocks and andesite intrusions, and have been subjected to freshwater conditions. © 2022